A8.15 ProS and Gas6 - two structurally related proteins with therapeutic effects in experimental arthritis, but via two different mechanisms. (13th February 2015) - Beermann, S; Waterborg, CEJ; van den Brand, BT; Bennink, MB; Koenders, MI; de Vries, M; Rothlin, CV; van de Loo, FAJ
Abstract : Protein S (ProS) and growth-arrest-specific protein 6 (Gas6) are both ligands for TAM receptors, a family of receptor tyrosin kinases consisting of Axl, Mertk and Tyro3. Activation of these receptors induces a negative feedback loop by inhibiting TLR- and cytokine receptor signalling. ProS, next to its function as a TAM receptor ligand, plays a role in coagulation where it acts as a cofactor of the anticoagulant Protein C. Due to the anti-inflammatory effects of Gas6 and ProS, they could be a promising treatment for different autoimmune disease such as rheumatoid arthritis (RA). In RA joints, activation of non-immunological pathways also takes place, like the coagulation cascade and factors of the coagulation cascade are described to cleave and activate complement factors. In this way the anti-coagulative function of ProS could positively affect RA pathology. We therefore investigated the therapeutic effect of Gas6 and ProS in experimental arthritis. Adenoviruses for overexpressing Gas6 or Pros1 genes were injected locally into the knee joints of mice in two different RA models: one day after the booster injection in the T-cell dependent collagen-induced arthritis (CIA) model or one day before the second injection of serum in the anti-GPI autoantibody driven KRN serum transfer model. Mice were sacrificed at day 31 or day 14, respectively and knee joints were taken for histology and synovial biopsies for cytokine profiling. In the CIA model, mice receiving adenoviruses encoding for either Pros1 or Gas6 showed reduced joint inflammation, bone and cartilage erosion in which the effect of Gas6 was more prominent than that of Pros1 . Furthermore, levels of pro-inflammatory cytokines in the synovium such as IL-6 and IL-1b and also MMP-9 and MMP-13 were reduced whereas expression of SOCS1 and protein levels of SOCS3, downstream molecules of TAM receptor signalling, were increased indicating a TAM receptor mediated mechanism. In KRN arthritis, inflammation, bone and cartilage erosion and osteophyte formation was strongly reduced in Pros1 treated mice, whereas Gas6 was completely ineffective in this model. Expression of cytokines like TNFa, IL-1b and MMP-13 in the synovium were decreased in mice receiving Pros1 whereas SOCS1 and SOCS3 expression remains unchanged, indicating a TAM receptor independent effect. In conclusion, Gas6 and ProS appear to interfere with the pathology of arthritis on two different levels. In CIA, both of them can induce anti-inflammatory TAM receptor signalling whereas in the KRN model, ProS presumably blocks the coagulation cascade and thereby prevents complement C5 activation.